Cognitive Evoked Potentials (P300): Is the Decision To Press a Button Always Conscious? - Klochkova, O; Gnezditsky, V (KnE Life Sciences, 2018)
Evoked cognitive potentials are a promising experimental technique that can be useful in diagnosis of various cognitive disorders, especially connected to the various memory impairments. Of particular interest to researchers is the study of the cognitive evoked potentials’ latency when recognition of various stimuli is involved. To study the physiological nature and functional role of evoked cognitive potentials observed during the reaction to stimuli, and to determine the degree of conscious control involved in this reaction, the experimental data were statistically analyzed to determine the numerical correlation between the working memory capacity and the cognitive potential’s latency. The cognitive EPs were measured for 166 healthy subjects and 63 others that had some pathological brain condition (discirculatory encephalopathy and other brain discirculatory disorders), varied by the age and gender. Measurements were done with the Neurosoft Neuro-MEP 4 computerized encephalography system, which implemented the standard method of large latency neural response measurement for P300 waves. Measurements were done in the setup where the subject had to recognize the significant stimuli and react to them by pressing a button. The significant stimulus was represented by a 2 kHz tone, while the insignificant stimuli were the frequently repeated 1 kHz tones. The brainwaves were registered in Cz-M1 and Cz-M2 outputs. This method allowed detection and latency measurements of the main response components N2, P3a P3ab and N3. Working memory capacity was determined by the number of words from a 10–15 word sets correctly reproduced shortly after exposures, as outlined by Luria. A statistically significant nonlinear correlation was observed between the memory capacity and the EP’s latency, which was fitted by a modified hyperbolic function. Additionally, greater latencies were observed for subjects suffering from the memory disorders, and much shorter latencies were in general noted for the male subjects as opposed to the female ones. One more interesting observation was that in many cases the absolute reaction time was less than the cognitive potential peak taken as a conscious decision, suggesting that it is in many cases an automatic reaction. Cognitive potentials measurements, being an instrumental method, allow a clinical psychologist much greater flexibility in his diagnostic repertory, as it can be used even in the cases where word tests cannot. Also, the reaction times shorter than the latency of conscious reaction to stimuli adds weight to the simultaneous codes theory of automatic reactions. Keywords: working memory capacity (WMC), regression line, nonlinear correlation, test less WMC estimates, cognitive processes, working memory, cognitive evoked potentials simultaneous codes, positional game, conscious cognitive comparison, P300